Investigation of the gold nanoparticles effects on the prostate dose distribution in brachytherapy: gel dosimetry and Monte Carlo method - Khosravi, Hossein; Hashemi, Bijan; Rahmani, Faezeh; Ebadi, Ahmad (Journal of Contemporary Brachytherapy, 2016)
Purpose: In this work, gold nanoparticles (GNPs) were embedded in the MAGIC-f polymer gel irradiated with the 192 Ir brachytherapy sources. Material and methods: At the first plexiglas phantom was made as the human pelvis. The GNPs were synthesized with 15 nm in diameter and 0.1 mM (0.0197 mg/ml) in concentration by using a chemical reduction method. Then, the MAGIC-f gel was synthesized. The fabricated gel was poured into the tubes located at the prostate (with and without the GNPs) locations of the phantom. The phantom was irradiated with 192 Ir brachytherapy sources for prostate cancer. After 24 hours, the irradiated gels was read by using Siemens 1.5 Tesla MRI scanner. Following the brachytherapy practices, the absolute doses at the reference points and isodose curves were extracted and compared by experimental measurements and Monte Carlo (MC) simulations. Results : The mean absorbed doses in the presence of the GNPs in prostate were 14% higher than the corresponding values without the GNPs in the brachytherapy. The gamma index analysis (between gel and MC) using 7%/7 mm was also applied to the data and a high pass rate achieved (91.7% and 86.4% for analysis with/without GNPs, respectively). Conclusions : The real three-dimensional analysis shows the comparison of the dose-volume histograms measured for planning volumes and the expected one from the MC calculation. The results indicate that the polymer gel dosimetry method, which developed and used in this study, could be recommended as a reliable method for investigating the dose enhancement factor of GNPs in brachytherapy.